2020
DOI: 10.1038/s41598-020-70414-2
|View full text |Cite
|
Sign up to set email alerts
|

One-pot simultaneous production and sustainable purification of fibrinolytic protease from Bacillus cereus using natural deep eutectic solvents

Abstract: www.nature.com/scientificreports/ (M1245)) were obtained from Himedia, India with a purity standard greater than 95%. All the chemicals used and their purification method is detailed in Table 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The purity fold obtained in this report was greater than the purity fold of pectinase (15.2) investigated by Amid et al using Triton X and sorbitol for phase separation 21 . A similar study on menthol based natural deep eutectic solvents (NADES) reported purity fold 21.2 for the recovery of fibrinolytic protease 2 .
Figure 5 Response surface methodology based optimization of SDES concentration, Salt concentration and pH of medium for effective recovery of fibrinolytic protease.
…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The purity fold obtained in this report was greater than the purity fold of pectinase (15.2) investigated by Amid et al using Triton X and sorbitol for phase separation 21 . A similar study on menthol based natural deep eutectic solvents (NADES) reported purity fold 21.2 for the recovery of fibrinolytic protease 2 .
Figure 5 Response surface methodology based optimization of SDES concentration, Salt concentration and pH of medium for effective recovery of fibrinolytic protease.
…”
Section: Resultsmentioning
confidence: 80%
“…Intravascular thrombosis is described as a pathophysiological disorder in which excessive accumulation of blood clots (thrombus) occurs throughout the blood vessels. This chronic condition obstructs blood flow to numerous internal organs and has been reported to be the major cause of cardiovascular abnormalities worldwide 1 , 2 . Conventionally, recombinant therapeutic enzymes such as streptokinase and urokinase are being used widely for treating these thrombotic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…The in uence of these salts on the phase ratio depends on its corresponding salting out capacity. It could be noted from the results that individual salt in combination with various NADES shows a diverse phase volume ratio in extractive fermentation 42 .…”
Section: Effect Of Choice Of Salt and Nades On Extraction Of Narringinasementioning
confidence: 98%
“…An 18.3-fold purification with specific activity of 52.4 U/mg was observed [28]. Maximum 21.2-fold purification with specific activity of 2607.8 U/mL was obtained on the subsequent purification of fibrinolytic protease from Bacillus cereus with an anion exchange column (DEAE-sepharose) [169].…”
Section: Recovery and Purification Of Fibrinolytic Enzymesmentioning
confidence: 98%